Molecular dynamics simulation of water transport through carbon nanotubes - Chen, Luwei. (2009)
Carbon nanotubes present an exciting area of research, with a large portion of current nanoscience research involved in carbon nanotubes. Due to their impressive mechanical, electrical, and transport properties, it is proposed for a variety of applications. An introduction of carbon nanotubes and their physical and thermal properties are reviewed in this report. This report also summarises a few properties of carbon nanotubes concluded from existing literature, namely, diffusivity of water, density, and hydrogen bond dynamics of confined water. An overview of desalination and various aspects of the Reverse Osmosis desalination process is provided. The limitations of current RO desalination processed are discussed and the possible application of Carbon nanotube in the desalination process is assessed.